2019
DOI: 10.1080/22221751.2019.1604084
|View full text |Cite
|
Sign up to set email alerts
|

Targeting host metabolism by inhibition of acetyl-Coenzyme A carboxylase reduces flavivirus infection in mouse models

Abstract: Flaviviruses are (re)-emerging RNA viruses strictly dependent on lipid metabolism for infection. In the search for host targeting antivirals, we explored the effect of pharmacological modulation of fatty acid metabolism during flavivirus infection. Considering the central role of acetyl-Coenzyme A carboxylase (ACC) on fatty acid metabolism, we analyzed the effect of three small-molecule ACC inhibitors (PF-05175157, PF-05206574, and PF-06256254) on the infection of medically relevant flaviviruses, namely West N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…For instance, both extracellular and intracellular arthropod-borne pathogens must salvage lipids from their hosts for survival ( Table 2 ). To this end, drugs targeting lipid metabolism have been shown to inhibit arboviral and parasitic infections ( Tewary et al, 2006 ; Bobenchik et al, 2013 ; Merino-Ramos et al, 2016 ; Choi et al, 2016 ; Jiménez de Oya et al, 2019 ). Thus, their use in humans is a promising area of research.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…For instance, both extracellular and intracellular arthropod-borne pathogens must salvage lipids from their hosts for survival ( Table 2 ). To this end, drugs targeting lipid metabolism have been shown to inhibit arboviral and parasitic infections ( Tewary et al, 2006 ; Bobenchik et al, 2013 ; Merino-Ramos et al, 2016 ; Choi et al, 2016 ; Jiménez de Oya et al, 2019 ). Thus, their use in humans is a promising area of research.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The activation of AMPK using these compounds also inhibits the infection of DENV and WNV [51,53], confirming the broad-spectrum antiviral potential of this kind of drugs. Results using a series of small-molecule inhibitors (PF-05175157, PF-05206574 and PF-06256254, Table 1) of acetyl-Coenzyme A carboxylase (ACC), the key enzyme of fatty acid metabolism, support the role of lipid metabolism and specifically fatty acid synthesis in ZIKV, DENV, and WNV infection [54]. One of these inhibitors, PF-05175157, which has undergone clinical trials in healthy volunteers (NCT01433380), and for the treatment of diabetes mellitus (NCT01792635), was tested against WNV in mouse models, showing a reduction of viremia and viral load in the kidney, suggesting the potential of these compounds for the treatment of flavivirus diseases.…”
Section: Lipids and Therapeutic Opportunities Against Zikv Infectionmentioning
confidence: 99%
“…Next, palmitate undergoes chain propagation to produce saturated FAs via FA elongase [43], as seen in Figure 7. It is common to suppress FA synthesis by inhibitors targeting related enzymes, which have been proven to decrease the replication of various viruses, including respiratory viruses [44] and flaviviruses [45]. Additionally, evidence has shown that drugs targeting ACC1 are effective for antiviral treatment [46][47][48].…”
Section: Discussionmentioning
confidence: 99%